Innovative CDR grafting and computational methods for PD-1 specific nanobody design - Devasani, Jagadeeswara Reddy; Guntuku, Girijasankar; Panatula, Nalini; Muthyala, Murali Krishna Kumar; Palla, Mary Sulakshana; Siahaan, Teruna J. (Frontiers in Bioinformatics, 2025)
IntroductionThe development of nanobodies targeting Programmed Cell Death Protein-1 (PD-1) offers a promising approach in cancer immunotherapy. This study aims to design and characterize a PD-1-specific nanobody using an integrated computational and experimental approach.MethodsAn in silico design strategy was employed, involving Complementarity-Determining Region (CDR) grafting to construct the nanobody sequence. The three-dimensional structure of the nanobody was predicted using AlphaFold2, and molecular docking simulations via ClusPro were conducted to evaluate binding interactions with PD-1. Physicochemical properties, including stability and solubility, were analyzed using web-based tools, while molecular dynamics (MD) simulations assessed stability under physiological conditions. The nanobody was produced and purified using Ni-NTA chromatography, and experimental validation was performed through Western blotting, ELISA, and dot blot analysis.ResultsComputational findings demonstrated favorable binding interactions, stability, and physicochemical properties of the nanobody. Experimental results confirmed the nanobody’s specific binding affinity to PD-1, with ELISA and dot blot analyses providing evidence of robust interaction.DiscussionThis study highlights the potential of combining computational and experimental approaches for engineering nanobodies. The engineered PD-1 nanobody exhibits promising characteristics, making it a strong candidate for further testing in cancer immunotherapy applications.